1986
DOI: 10.1056/nejm198611203152103
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Transmission of Diabetic Alleles within the HLA Gene Complex

Abstract: Several studies suggest a higher incidence of insulin-dependent diabetes mellitus (IDDM) among the offspring of men with the disease than among those of female diabetics. Differential transmission by the father of genes that predispose to diabetes may explain this phenomenon. To test this hypothesis, we examined parent-to-offspring transmission of HLA haplotypes and DR (D-related) alleles in 107 nuclear families in which a child had IDDM. We observed that fathers with a DR4 allele were significantly more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
4
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 34 publications
2
44
4
1
Order By: Relevance
“…Overtransmission of DR4 from non-diabetic fathers to both diabetic and non-diabetic offspring has also been claimed [28] but reports from several investigators [16,[29][30][31] as well as our own data, have failed to show any significant differences of transmission between parents. On the other hand, the overtransmission reported for paternal [32] or maternal [33] AIB8 (DR3) haplotypes related to the sex of the offspring in diabetic and healthy families still remains to be confirmed.…”
Section: Discussionmentioning
confidence: 51%
“…Overtransmission of DR4 from non-diabetic fathers to both diabetic and non-diabetic offspring has also been claimed [28] but reports from several investigators [16,[29][30][31] as well as our own data, have failed to show any significant differences of transmission between parents. On the other hand, the overtransmission reported for paternal [32] or maternal [33] AIB8 (DR3) haplotypes related to the sex of the offspring in diabetic and healthy families still remains to be confirmed.…”
Section: Discussionmentioning
confidence: 51%
“…The mechanism by which Type I diabetes is more frequent in fathers of Type I diabetes children is poorly understood. An increase in the paternal transmission of HLA susceptibility genes was suggested earlier [25,26], but a recent study of 172 multiplex diabetic pedigrees from the United Kingdom found no evidence for this [27]. It is possible, that an interaction between the diabetic mother and fetus takes place which provides protection for the offspring in later life.…”
Section: Discussionmentioning
confidence: 97%
“…Third, fetuses exposed to maternal diabetes could be protected from subsequent manifestation of T1D and thus could also lead to the observed preferential transmission [Warram et al, 1984]. Fourth, the diabetogenic genes may be preferentially transmitted from fathers to offspring, regardless of whether the fathers are themselves diabetic or not [Vadheim et al, 1986]. Data from 107 nuclear families appeared to support this hypothesis, which was confirmed by Field [1989Field [ , 1994.…”
Section: Introductionmentioning
confidence: 83%